Using satellite images in updating topographic maps (An applicated study on Al-Bahlolia district) (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
The science and art of producing maps had been subjected to the changes as a result of new recent techniques developments at space photogrammetry, that lead to appearance of programs and applications in the computer's world. This associated with the advent of information age and Geographic information system that changed the traditional topographic map from just a map to an analyzing and viewing tool. All Syrian Topographic maps are old, out dated, and largely exist in paper form. Due to the high cost of aerial photography, These maps have not been updated for many years and such are not useful for planning. Therefore, there is an urgent need to produce new maps using high resolution satellite images. The research put a method for updating topographic maps of Al-Bahlolia district which have scales (1/50000) and (1/200000), By using Cartosat1 images. After updating, The results were that there is increasing in the area of planted land. In addition to building developments, increasing of length and density of roads between and inside villages. Contour lines also have been generated automatically, so efforts and time were be saved.